Detection of anisakids (Nematoda, Anisakidae) in food and human clinical samples in Argentina - Degese, María Fernanda (2019)
Human anisakidosis is caused by the ingestion of anisakid third-stage larvae of the genera Anisakis, Pseudoterranova, Contracaecum, and Hysterothylacium, present in raw or undercooked fish and shellfish. The members of the complex Anisakis simplex, followed by those of the Pseudoterranova decipiens complex, are the most common anisakids infecting humans. In Argentina, infective larvae of these nematode species, have been identified in marine and freshwater fish. However, there are few human cases of anisakidosis from which the involved species, has not been documented yet. In this study, we reported the detection of anisakids in food and clinical samples from patients of Argentina. Nine samples of larvae were analyzed: two from clinical samples removed orally by patients, and seven found in raw, undercooked and cooked fish. The larvae from the two clinical samples were identified as Pseudoteranova cattani whereas larvae of Anisakis pegreffii, Anisakis sp., and P. cattani were found in food.